Preparation method of zirconia microspheres for polishing
By combining gel curing and forming technology and membrane emulsification technology, zirconia microspheres were prepared, which solved the problems of uneven particle size and easy adhesion of zirconia microspheres in the prior art, achieved the uniformity and controllability of microspheres, and broadened their application range.
Patent Information
- Application Number
- CN202510096612.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-22
AI Technical Summary
It is difficult to prepare zirconia microspheres with uniform particle size and controllable size in the prior art. Especially in microspheres with diameters below 50 μm, there are problems such as uneven particle size distribution and easy adhesion.
By combining gel curing and film emulsification technology, a water-based slurry and an oil-phase pre-emulsifier with an emulsifier added as the dispersed phase, and a CaCl2 curing liquid as the mobile phase, a stable water-in-oil (W/O) is formed through the alumina film, and a catalyst is added, and finally a zirconia microsphere blank is obtained by cleaning and drying.
It greatly shortens the curing reaction time, improves the size uniformity and controllability of the zirconia microsphere blank, solves the problem of easy curing of emulsification cross-linking reaction in traditional methods, and broadens the application range of zirconia microspheres.
Smart Images

Figure CN119528567A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of zirconium oxide ball preparation, and in particular to a method for preparing zirconium oxide microspheres for polishing. Background Art
[0002] Y 2 O 3 Stable zirconia microspheres have good development prospects due to their good chemical stability and mechanical strength. At the same time, due to the further improvement of zirconia particle size requirements in various industries, the demand for wear resistance of zirconia microspheres with a diameter of less than 50μm is becoming more and more urgent. The existing preparation methods of zirconia microspheres with a diameter of less than 50μm are mainly traditional preparation methods of microspheres such as mechanical stirring, ultrasound, microfluidization, high-speed homogenization emulsification and spray drying. There are problems such as poor monodispersity of particle size, uneven size of microspheres, and easy adhesion of microspheres. This is because the shear force or ultrasound at each point of the dispersed phase is uneven, and it is difficult to control the uniformity of the microsphere particle size. Therefore, how to prepare zirconium dioxide microspheres with uniform particle size and controllable size is still a difficulty.
[0003] CN201410177510 discloses a high-speed homogenization emulsification method: adding dissolved PCL to rapidly stirred water to form an emulsion to obtain microspheres. The biggest problem with this method is the low yield. The particle size distribution of the microspheres dispersed by rapid mechanical stirring is too wide. Screening is required to obtain microspheres of 30-80 μm, and the yield is low and unstable. CN106830927A discloses a method for preparing zirconium oxide ceramic microspheres by titration molding, which mixes ceramic powder with hot-melt mixed glue, and forms ceramic microsphere green bodies by air cooling during the dripping process using a titration device. Since the cooling and solidification of the microspheres is carried out in the air, the droplets are pulled by gravity and will be elongated to a certain extent in the vertical direction. The sphericity is difficult to ensure, and there is a problem of easy blockage. Summary of the invention
[0004] In order to overcome the deficiencies in the prior art, the present invention provides a method for preparing zirconium oxide microspheres for polishing.
[0005] To achieve the above object, the present invention provides a method for preparing zirconium oxide microspheres for polishing, and the steps are as follows: Step 1, weigh N,N'-methylenebisacrylamide, acrylamide, a dispersant and deionized water in proportion, mix and stir to obtain slurry A; Step 2: 3Y-ZrO 2 The powder and slurry A are mixed in proportion and then ball-milled for a certain period of time. After the median particle size D50 of the ball-milled slurry is qualified, a certain amount of defoamer and initiator are added to obtain slurry B; Step 3, adding a certain amount of emulsifier to the organic solvent to obtain oil phase C; Step 4: adding slurry B to oil phase C and mixing to obtain pre-emulsion D; Step 5: Add the pre-emulsion D to the emulsification device, start cooling and stirring, open the valve after a period of time, and the pre-emulsion enters the alumina membrane device, passes through the alumina membrane under nitrogen pressure, and obtains emulsion droplets under the action of magnetic stirring. The droplets are in the solidifying liquid to obtain a microsphere precursor, and then turn on the catalyst addition pump to obtain a solidified zirconium oxide microsphere blank; Step 6: Clean, dry, pre-sinter and sinter the microsphere blank at low temperature to obtain 30-50 μm zirconium oxide microspheres.
[0006] Preferably, the emulsifier is one or both of Span 80 and Tween 80; the organic solvent is one or more of dimethyl silicone oil, paraffin and soybean oil, and the volume ratio of emulsifier: organic solvent is 0.7-2.5:100.
[0007] Preferably, the volume ratio of the emulsifier to the organic solvent is 0.7-2.5:100.
[0008] Preferably, the 3Y-ZrO 2 The mass ratio of powder: slurry A is 65-75:25-35, and the median particle size D50 of the slurry after ball milling is less than 0.15μm; the mass ratio of N,N'-methylenebisacrylamide:acrylamide:initiator in slurry A is specifically 1:20:1; dispersant: 3Y-ZrO 2 The specific powder mass ratio is 0.5-2.0:100, and the volume ratio of catalyst:curing liquid is 0.015~0.025:100.
[0009] Preferably, the volume ratio of the slurry B to the oil phase C is 1:5-100.
[0010] Preferably, the stirring is mechanical stirring, and the stirring speed is 1000-1100 r / min; the stirring time is 5-15 min.
[0011] Preferably, the pore size of the aluminum oxide membrane is 10-25 μm and the aluminum oxide membrane is immersed in the oil phase C for more than 2 hours.
[0012] Preferably, the nitrogen pressure is 0.25-0.60 MPa; and the magnetic stirring speed is 30-50 r / min.
[0013] Preferably, the low-temperature pre-sintering temperature is 490-800° C., and the holding time is 2-2.5 hours; the high-temperature sintering temperature is 1200-1300° C., and the holding time is 2-2.5 hours.
[0014] Preferably, the dispersant is ammonium citrate; the catalyst is cuprous chloride; the initiator is ammonium persulfate; the defoamer is tributyl phosphate; the curing liquid is 2% by mass CaCl 2 solution, wherein the volume ratio of defoamer:slurry B is 0.05-0.1:100.
[0015] The beneficial effects of the present invention are as follows: 1. Combine gel solidification technology and membrane emulsification technology, use water phase slurry and oil phase-pre-emulsion liquid with emulsifier as dispersed phase, CaCl 2 The solidifying liquid is used as the mobile phase, passing through the alumina film to form a stable water-in-oil (W / O), and then the catalyst is added. Finally, the oil phase is washed away and dried to obtain the zirconium oxide microsphere blank, which greatly shortens the curing reaction time and improves the size uniformity and controllability of the blank (the size of the alumina film and the size of the microsphere blank is about 1:3); 2. The initiator is introduced into the pre-emulsion liquid, and the required environment needs to be 15-25°C. The method of the present invention adds a cooling cycle to the device, which solves the problem of easy solidification during the emulsification cross-linking reaction in the gel curing process; 3. The method of the present invention is relatively simple to operate, easy to implement, and has impressive results. The zirconia microspheres have great application potential in the fields of grinding and dispersing high-value-added ceramics with high product purity requirements, biochemistry, and pharmaceutical industries, thus broadening the application scope of zirconia microspheres. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a flow chart for preparing zirconium oxide microspheres in the present invention; Figure 2 This is an electron microscope SEM picture of the zirconium oxide microspheres obtained in Example 1 of the present invention; Figure 3 This is an electron microscope SEM picture of the zirconium oxide microspheres obtained in Example 2 of the present invention; Figure 4 This is an electron microscope SEM picture of the zirconium oxide microspheres obtained in Example 3 of the present invention; Figure 5 This is an electron microscope SEM picture of the zirconium oxide microspheres obtained in Example 4 of the present invention; Figure 6 This is an electron microscope SEM picture of the zirconium oxide microspheres obtained in Reference Example 1 of the present invention; Figure 7 This is an electron microscope SEM picture of the zirconium oxide microspheres obtained in Reference Example 2 of the present invention. DETAILED DESCRIPTION
[0017] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present application will be further described below in conjunction with specific embodiments. Although the present invention has described several specific implementations, the present invention is not limited by the described implementations. At the same time, researchers in the technical field to which the present invention belongs cannot make modifications and improvements within the scope of protection determined by the claims of the present invention and their equivalents.
[0018] The mechanical properties of zirconium oxide microspheres such as sphericity, density and wear resistance were tested. Among them, the laser diffraction method was used to measure the sphericity; the Archimedes drainage method was used to measure the density; and the wear resistance was tested by placing 1kg of the grinding balls to be tested in a 1L polyurethane tank, adding 150g of water, 300g of zirconium silicate (zircon sand), and 2g of sodium tripolyphosphate, covering it, fixing it on the turntable in the rapid mill and grinding it continuously for 5h, taking out the grinding balls, washing them, drying them, and weighing them. The material wear (Rm) of qualified grinding balls is required to be less than 1.5μg / g / 5h.
[0019] Example 1 Weigh 0.6 g N,N'-methylenebisacrylamide, 12 g acrylamide, 0.06 g dispersant ammonium citrate and 87.34 g deionized water, mix and stir to obtain slurry A1; press 3Y-ZrO 2 Powder (3 mol% yttria-stabilized zirconium oxide powder): slurry A1 mass ratio = 60:40, mix and then ball-mill, the median particle size of the ball-milled slurry D50 = 0.111 μm, add 0.06% of the volume of defoamer tributyl phosphate relative to the volume of slurry B and 0.6% of the mass of initiator ammonium persulfate relative to the mass of slurry A to obtain slurry B1; add 1% of Span 80 relative to the volume of dimethyl silicone oil to dimethyl silicone oil to obtain oil phase C1; B1 and C1 are mixed at a volume ratio of 1:7 to obtain pre-emulsion D1; add pre-emulsion D1 to an emulsifier ( Figure 1 ), start cooling and stirring, stirring speed is 1000r / min, open the valve after 5min, the pre-emulsion enters the alumina membrane (membrane pore size is 15μm) device, passes through the alumina membrane under nitrogen pressure (pressure is 0.30MPa), and under the action of magnetic stirring (stirring speed is 30r / min), emulsion droplets are obtained. The droplets are in 2%CaCl 2 The microsphere precursor is obtained in the solidifying liquid, and then the catalyst adding pump (catalyst cuprous chloride 0.015) is turned on to obtain the zirconium oxide microsphere blank.
[0020] The microsphere green blank was cleaned, dried, pre-sintered at 500°C, kept warm for 2 hours, and finally sintered at 1200°C, kept warm for 2.5 hours. The procedures of pre-sintering and high-temperature sintering are shown in Tables 1 and 2 below.
[0021] Zirconia microspheres are pre-sintered. The actual temperature control program is shown in Table 1. When the set temperature is 90°C, the heating rate is 1.8°C / min. The heating time in this stage is 50min. After reaching 90°C, keep the temperature for 120min. The total time for this stage is 170min. Then heat up from 90°C to 500°C, the heating rate is 0.8°C / min, this stage takes 512.5min, and the total time is 682.5min. Then keep warm at 500°C, the holding time is 360min, and the total time is 1042.5min. Finally, cool down to 100°C at a rate of -10°C / min, and the cooling time is 40min. The entire pre-sintering takes 1082.5min.
[0022] Zirconia microspheres are pre-sintered and then sintered. The actual temperature control program is shown in Table 2. When the set temperature is 50°C, the heating rate is 1°C / min. The heating time in this stage is 50min. After reaching 50°C, keep at this temperature for 50min. This stage is completed, and the total time is 100min. Then the temperature is increased from 50°C to 1000°C at a heating rate of 10°C / min. This stage takes 95min, that is, 195min. Then, it is kept at 1000°C for 60min. This process takes 255min. Then, it is heated from 1000°C to 1200°C at a heating rate of 1°C / min. This stage takes 200min, that is, 455min. Then, it is kept at 1200°C for 60min, which takes 515min. Finally, it is cooled to 100°C at a rate of -10°C / min, which takes 120min. The whole process takes 635min.
[0023] Table 1 Zirconia microsphere pre-sintering process parameters , Table 2 Process parameters of zirconia microspheres after pre-sintering and re-sintering .
[0024] Different emulsifier Span 80 concentrations result in different microsphere green body sizes. This example adjusts the emulsifier concentration and also conducts research on zirconium oxide microspheres A1-1 and A1-2. The conditions and results are shown in Table 3: Table 3 , Under the same operating conditions, the particle size of the emulsion prepared by adding a higher concentration of emulsifier is smaller than that of the emulsion prepared by adding a lower concentration of emulsifier. The higher the concentration of emulsifier in the dispersed phase, the better it can be adsorbed on the surface of the dispersed phase. The probability of emulsion droplets aggregating and growing is lower, so the average particle size is smaller. Therefore, the concentration of the emulsifier has a certain effect on the particle size of the droplets. At the same time, the concentration of the emulsifier should not be too high, otherwise a large amount of residual emulsifier will become impurities and exist in the dispersed system.
[0025] Example 2 Weigh 0.6 g N,N'-methylenebisacrylamide, 12 g acrylamide, 0.06 g dispersant and 87.34 g deionized water, mix and stir to obtain slurry A2; press 3Y-ZrO 2 The mass ratio of powder to slurry A2 was 62:38, and the mixture was ball-milled. The median particle size of the ball-milled slurry was D50 = 0.114 μm. 0.06% defoamer and 0.6% initiator were added to obtain slurry B2. 1.1% Tween 80 was added to dimethyl silicone oil to obtain oil phase C2. B2 and C2 were mixed at a volume ratio of 1:10 to obtain pre-emulsion D2. The pre-emulsion D2 was added to the emulsification device, and cooling and stirring were started. The stirring speed and stirring time were set according to Table 4, and then the valve was opened. The pre-emulsion entered the alumina membrane (membrane pore size was 16 μm) device, passed through the alumina membrane under nitrogen pressure (pressure was 0.30 MPa), and under the action of magnetic stirring (stirring speed was 30 r / min), emulsion droplets were obtained. The droplets were in 2% CaCl 2 The microsphere precursor was obtained in the solution, and then the catalyst addition pump (catalyst 0.022) was turned on to obtain the zirconia microsphere blank; the microsphere blank was cleaned, dried, pre-sintered at 600℃, kept warm for 2h, and finally sintered at 1300℃, kept warm for 2.5h. The procedures of pre-sintering and high-temperature sintering are shown in Tables 1 and 2.
[0026] Different stirring speeds and times result in different sizes of microsphere green bodies. This embodiment adjusts the stirring speed and time, and also conducts research on zirconium oxide microspheres B1-1 and B1-2. The conditions and results are shown in Table 4: Table 4 , Under the same operating conditions, the higher the mechanical stirring speed, the smaller the size of the pre-emulsified droplets in the dispersed phase, so the average particle size is smaller. Therefore, the stirring speed has a certain effect on the particle size of the droplets. The mechanical stirring time has little effect within a certain range. At the same time, the mechanical stirring speed and time should not be too high, otherwise the pre-emulsified droplets will be destroyed in the dispersed phase.
[0027] Example 3 Weigh 0.5 g N,N'-methylenebisacrylamide, 10 g acrylamide, 0.05 g dispersant and 89.45 g deionized water, mix and stir to obtain slurry A3; press 3Y-ZrO 2 The mass ratio of powder to slurry A3 was 60:40, and the mixture was ball-milled. The median particle size of the ball-milled slurry was D50 = 0.113 μm. 0.05% defoamer and 0.5% initiator were added to obtain slurry B3. 1% Span 80 was added to dimethyl silicone oil to obtain oil phase C3. B3 and C3 were mixed at a volume ratio of 1:5 to obtain pre-emulsion D3. The pre-emulsion D3 was added to the emulsification device, and cooling and stirring were started. The stirring speed was 1000 r / min. After 5 minutes, the valve was opened, and the pre-emulsion entered the alumina membrane (membrane pore size was 15 μm) device, passed through the alumina membrane under the set nitrogen pressure, and obtained emulsion droplets under the action of magnetic stirring (stirring speed was 40 r / min). The droplets were stirred at 2% CaCl 2 The microsphere precursor was obtained in the solution, and then the catalyst addition pump (catalyst 0.022) was turned on to obtain the zirconia microsphere blank; the microsphere blank was cleaned, dried, pre-sintered at 600℃, kept warm for 2h, and finally sintered at 1300℃, kept warm for 2.5h. The procedures of pre-sintering and high-temperature sintering are shown in Tables 1 and 2.
[0028] Different gas pressures result in different microsphere green body sizes. In this embodiment, the gas pressure was adjusted and the zirconium oxide microspheres C1-1 and C1-2 were also studied. The conditions and results are shown in Table 5: Table 5 , Since nitrogen is applied in the present invention, two gases will appear on both sides of the membrane, one side is nitrogen pressure and the other side is atmospheric pressure. The difference between the two pressures is the membrane surface pressure difference. Only when the nitrogen pressure is greater than the atmospheric pressure can the droplets come out of the alumina membrane. In the present invention, the aqueous phase slurry and the oil phase-pre-emulsion liquid with the emulsifier added constitute the dispersed phase, and CaCl 2 The solidifying liquid is the mobile phase. Under the same operating conditions, although the pore size of the alumina membrane is the main factor determining the emulsion particle size, the membrane surface pressure difference is also one of the key factors affecting the emulsion particle size, because the size of the membrane surface pressure difference controls the flow rate and flux of the dispersed phase. When the gas pressure is small, the membrane surface pressure difference is small, the flux is low, the slurry passes through the membrane slowly and lasts for a long time, the droplets are easy to agglomerate, the average particle size is large and it is easy to block the membrane; when the membrane surface pressure difference is large, the dispersed phase will be dispersed into the continuous phase in the form of a jet, the pre-emulsion does not fully contact the alumina membrane, and smaller droplets are formed with poor roundness.
[0029] Example 4 Weigh 0.6 g N,N'-methylenebisacrylamide, 12 g acrylamide, 0.06 g dispersant and 87.34 g deionized water, mix and stir to obtain slurry A4; press 3Y-ZrO 2 The mass ratio of powder to slurry A4 was 62:38, and the mixture was ball-milled. The median particle size of the ball-milled slurry was D50 = 0.117 μm. 0.06% defoamer and 0.6% initiator were added to obtain slurry B4. 1% Span 80 was added to dimethyl silicone oil to obtain oil phase C4. B4 and C4 were mixed at a volume ratio of 1:8 to obtain pre-emulsion D4. The pre-emulsion D4 was added to the emulsification device, and cooling and stirring were started. The stirring speed was 1000 r / min. After 6 minutes, the valve was opened, and the pre-emulsion entered the alumina membrane (membrane pore size was 15 μm) device, and passed through the alumina membrane under nitrogen pressure (pressure was 0.30 MPa). Under the action of magnetic stirring, emulsion droplets were obtained. The droplets were stirred in 2% CaCl 2 The microsphere precursor was obtained in the solution, and then the catalyst addition pump (catalyst 0.022) was turned on to obtain the zirconia microsphere blank; the microsphere blank was cleaned, dried, pre-sintered at 500℃, kept warm for 2h, and finally sintered at 1200℃, kept warm for 2.5h. The procedures of pre-sintering and high-temperature sintering are shown in Tables 1 and 2.
[0030] Different magnetic stirring speeds result in different microsphere green body sizes. This embodiment adjusts the magnetic stirring speed and also conducts research on zirconium oxide microspheres D1-1 and D1-2. The conditions and results are shown in Table 6: Table 6 , Under the same operating conditions, the flow rate of the continuous phase is an important factor affecting the droplet size and roundness. The droplet size can be controlled by adjusting the continuous phase velocity. Different continuous phase flow rates produce different shear forces, which affect the size and speed of the dispersed phase when it leaves the membrane surface, thus affecting the droplet size of the dispersed phase in the emulsion and the flux of the dispersed phase through the membrane. The continuous phase needs to exceed a certain critical flow rate, and the membrane surface shear force generated can overcome the interfacial tension of the dispersed phase droplets on the membrane surface, so that the dispersed phase droplets that have passed through the membrane pores can leave the membrane surface and enter the continuous phase. When the speed of the magnetic stirrer is low, the shear force generated is small, and the dispersed phase on the membrane surface cannot be brought into the continuous phase in time. The dispersed phase droplets gather and grow on the membrane surface, resulting in a larger average particle size of the droplets passing through the membrane, that is, the size of the green body of the microspheres after solidification is larger; when the speed of the magnetic stirrer is high, the emulsifier in the continuous phase cannot form a stable protective film on the surface of the dispersed phase droplets, causing the dispersed phase droplets to undergo secondary aggregation after dispersion, resulting in an increase in the emulsion particle size.
[0031] Reference example 1 Weigh 0.6 g N,N'-methylenebisacrylamide, 12 g acrylamide, 0.06 g dispersant and 87.34 g deionized water, mix and stir to obtain slurry A1'; press 3Y-ZrO 2 The mass ratio of powder to slurry A1' was 60:40, and the mixture was ball-milled. The median particle size of the ball-milled slurry was D50 = 0.120 μm. 0.06% defoamer and 0.6% initiator were added to obtain slurry B1'; 1% emulsifier Span 80 was added to dimethyl silicone oil to obtain oil phase C1'; B1' and C1' were mixed at a volume ratio of 1:7 to obtain pre-emulsion D1'; the pre-emulsion D1' was added to the emulsification device, and cooling and stirring were started. The stirring speed was 1000 r / min. After 5 minutes, the valve was opened, and the pre-emulsion entered the alumina membrane (membrane pore size was 15 μm) device, passed through the alumina membrane under nitrogen pressure (pressure was 0.20 MPa), and under the action of magnetic stirring (stirring speed was 30 r / min), emulsion droplets were obtained. The droplets were in 2% CaCl 2 The microsphere precursor was obtained in the solution, and then the catalyst addition pump (catalyst 0.015) was turned on to obtain a zirconia microsphere blank with an average particle size of 46.2μm; the microsphere blank was cleaned, dried, pre-sintered at 500℃, kept warm for 2h, and finally sintered at 1200℃, kept warm for 2.5h. The procedures of pre-sintering and high-temperature sintering are shown in Tables 1 and 2.
[0032] The sphericity of the obtained zirconia microspheres is 0.875 and the density is 6.028 g / cm 3 , the abrasion loss is 4.17ug / g.
[0033] Reference example 2 Weigh 0.6 g N,N'-methylenebisacrylamide, 12 g acrylamide, 0.06 g dispersant and 87.34 g deionized water, mix and stir to obtain slurry A2'; press 3Y-ZrO 2 The mass ratio of powder to slurry A2' was 60:40, and the mixture was ball-milled. The median particle size of the ball-milled slurry was D50 = 0.114 μm. 0.06% defoamer and 0.6% initiator were added to obtain slurry B2'; 1% emulsifier Span 80 was added to dimethyl silicone oil to obtain oil phase C2'; B2' and C2' were mixed at a volume ratio of 1:7 to obtain pre-emulsion D2'; the pre-emulsion D2' was added to the emulsification device, and cooling and stirring were started. The stirring speed was 1000 r / min. After 5 minutes, the valve was opened, and the pre-emulsion entered the alumina membrane (membrane pore size was 15 μm) device, passed through the alumina membrane under nitrogen pressure (pressure was 0.30 MPa), and under the action of magnetic stirring (stirring speed was 80 r / min), emulsion droplets were obtained. The droplets were in 2% CaCl 2The microsphere precursor was obtained in the solution, and then the catalyst addition pump (catalyst 0.015) was turned on to obtain a zirconia microsphere blank with an average particle size of 54.6μm; the microsphere blank was cleaned, dried, pre-sintered at 500℃, kept warm for 2h, and finally sintered at 1200℃, kept warm for 2.5h. The procedures of pre-sintering and high-temperature sintering are shown in Tables 1 and 2.
[0034] The sphericity of zirconia microspheres is 0.921 and the density is 6.034g / cm 3 , the abrasion is 3.24ug / g.
[0035] Characterization example The particle size, density, sphericity and abrasion of the ball mill slurry of Examples 1-4 and Reference Examples 1-2 were analyzed by a particle size analyzer, a density meter and a laser diffractometer, and the results are shown in Tables 7 and 8; the electron microscope (SEM) images of the zirconia microspheres obtained in Examples 1-4 and Reference Examples 1-2 are shown in Figure 2-Figure 7 .
[0036] It can be seen from Table 7 and Table 8 that the sphericity of the microspheres obtained in Examples 1-4 is higher, while the sphericity of the microspheres obtained in the reference example is lower, indicating that there is a significant difference in mechanical properties between the examples and the reference example; at the same time, the wear of the zirconia microspheres obtained in the examples is significantly lower than that in the reference example. Table 7 Particle size of slurry B in different embodiments and reference examples , Table 8 Density and wear of different embodiments and reference examples .
[0037] The method of the present invention combines the gel solidification forming technology and the membrane emulsification technology, uses the pre-emulsion obtained by the water-based slurry and the oil phase with the emulsifier as the dispersed phase, and CaCl 2The solidifying liquid is used as a mobile phase to form a stable water-in-oil (W / O). Under the coordination of mechanical stirring and magnetic stirring, an inert gas-nitrogen is used to pass through the aluminum oxide film, and then a catalyst is added. Finally, the oil phase is washed and removed, and the zirconium oxide microsphere blank is obtained by drying, which greatly shortens the curing reaction time and improves the size uniformity and controllability of the blank. The initiator is introduced into the pre-emulsified liquid, and the required environment needs to be 15-25° C. The method of the present invention adds cooling water circulation to the device, which solves the problem of extremely easy solidification during the emulsification cross-linking reaction in the gel curing process. In addition, the addition of the emulsifier can significantly reduce the interfacial tension between the membrane-dispersed phase, the dispersed phase-continuous phase, etc., promotes the dispersion of the dispersed phase droplets, and the emulsifier forms a protective film on the surface of the dispersed phase droplets. The emulsified droplets repel each other, which can effectively prevent the droplets from growing due to aggregation. Therefore, the addition of emulsifier can improve the stability of the dispersion system, thereby improving the emulsification efficiency; the catalyst cuprous chloride not only plays an antioxidant and coordination complexing role, but also can quickly solidify the microsphere precursor in the mobile phase, which can well control the size and uniformity of the blank, and solve the problem of blocking the membrane port when preparing microspheres in the traditional gel solidification and forming, in which the catalyst azobisisobutyronitrile and other catalysts generate highly active centers to trigger the exothermic reaction of the monomer, and the magnetic stirring speed is too fast, which will make the particle size of the microspheres uneven before solidification, and easy to stick together during sintering, as shown in Reference Example 2. Finally, the combination of low-temperature pre-sintering and high-temperature sintering not only eliminates the influence of the mobile phase that has not been cleaned in the micropores of the microsphere blank on the sintering process, but also promotes the solid solution of yttrium oxide and alumina and crystallization of grain boundaries to improve the strength of the grain boundary phase, further improve the density of zirconia microspheres, and obtain low-wear zirconia microspheres.
[0038] The present invention relates to a preparation method of zirconium oxide microspheres for polishing, and the specific steps are as follows: step 1, weighing N,N'-methylenebisacrylamide, acrylamide, a dispersant and deionized water in proportion, mixing and stirring to obtain slurry A; step 2, mixing 3Y-ZrO 2 (Contains 3% molY 2 O 3The zirconium oxide (zirconia, the same below) powder and slurry A are mixed in proportion and then ball-milled for a certain period of time. After the median particle size D50 of the ball-milled slurry is qualified, a certain amount of defoamer and initiator are added to obtain slurry B; step three, a certain amount of emulsifier is added to the organic solvent to obtain oil phase C; step four, slurry B is added to oil phase C for mixing to obtain pre-emulsion D; step five, the pre-emulsion D is added to the emulsification device, cooling and stirring are turned on, and the valve is opened after a period of time, and the pre-emulsion enters the alumina membrane device, passes through the alumina membrane under nitrogen pressure, and obtains emulsion droplets under the action of magnetic stirring. The droplets are in the solidifying liquid to obtain a microsphere precursor, and then the catalyst addition pump is turned on to obtain a solidified zirconium oxide microsphere blank; step six, the microsphere blank is cleaned, dried, low-temperature pre-sintered and high-temperature sintered.
[0039] The method of the present invention combines gel solidification forming technology with membrane emulsification technology, designs and builds a membrane emulsification rapid prototyping device for zirconium oxide microspheres, adopts the membrane emulsification rapid prototyping device to form a zirconium oxide microsphere blank, and controls the size of the microsphere particle size by membrane pore size, external pressure size, stirring speed and stirring time. The zirconium oxide microsphere blank is pre-sintered and sintered to obtain zirconium oxide microspheres with a size of 30 to 50 μm and uniform particle size. The preparation method of the present invention is suitable for industrial-scale production, so as to better promote the application and development of zirconium oxide microspheres, especially in the application space of grinding and dispersion of high-value-added ceramics with high product purity requirements, biochemistry, pharmaceutical industry and other fields.
[0040] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing zirconium oxide microspheres for polishing, characterized in that: The steps are as follows: Step 1, weigh N,N'-methylenebisacrylamide, acrylamide, a dispersant and deionized water in proportion, mix and stir to obtain slurry A; Step 2: 3Y-ZrO2 powder and slurry A are mixed in proportion and then ball-milled for a certain period of time. After the median particle size D50 of the ball-milled slurry is qualified, a certain amount of defoamer and initiator are added to obtain slurry B; Step 3, adding a certain amount of emulsifier to the organic solvent to obtain oil phase C; Step 4: adding slurry B to oil phase C and mixing to obtain pre-emulsion D; Step 5: Add the pre-emulsion D to the emulsification device, start cooling and stirring, open the valve after a period of time, and the pre-emulsion passes through the alumina membrane under nitrogen pressure. Under the action of magnetic stirring, emulsion droplets are obtained. The droplets are in the solidifying liquid to obtain a microsphere precursor, and then the catalyst addition pump is turned on to obtain a solidified zirconium oxide microsphere blank; Step 6: Clean, dry, pre-sinter and sinter the microsphere blank at low temperature to obtain 30-50 μm zirconium oxide microspheres.
2. The method according to claim 1, characterized in that: The emulsifier is one or both of Span 80 and Tween 80; the organic solvent is one or more of dimethyl silicone oil, paraffin and soybean oil; the volume ratio of emulsifier: organic solvent is 0.7-2.5:
100.
3. The method according to claim 1, characterized in that: The volume ratio of the emulsifier to the organic solvent is specifically 0.7-2.5:
100.
4. The method according to claim 1, characterized in that: The mass ratio of 3Y-ZrO2 powder to slurry A is 65-75:25-35, and the median particle size D50 of the slurry after ball milling is less than 0.15 μm; the mass ratio of N,N'-methylenebisacrylamide to acrylamide to initiator in slurry A is specifically 1:20:1; The mass ratio of dispersant: 3Y-ZrO2 powder is specifically 0.5-2.0:100, and the volume ratio of catalyst: solidifying liquid is 0.015~0.025:
100.
5. The method according to claim 1, characterized in that: The volume ratio of the slurry B to the oil phase C is specifically 1:5~100.
6. The method according to claim 1, characterized in that: The stirring is mechanical stirring, and the stirring speed is 1000-1100r / min; the stirring time is 5-15min.
7. The method according to claim 1, characterized in that: The pore size of the aluminum oxide membrane is 10-25 μm and the aluminum oxide membrane needs to be immersed in the oil phase C for more than 2 hours.
8. The method according to claim 1, characterized in that: The nitrogen pressure is 0.25-0.60 MPa; the magnetic stirring speed is 30-50 r / min.
9. The method according to claim 1, characterized in that: The low-temperature pre-sintering temperature is 490-800°C, and the insulation time is 2-2.5h; the high-temperature sintering temperature is 1200-1300°C, and the insulation time is 2-2.5h.
10. The method according to claim 1, characterized in that: The volume ratio of defoamer: slurry B is 0.05-0.1:100.
Citation Information
Patent Citations
Manufacturing method of a membrane and a membrane thereof, for emulsification
CA2652371A1
Polymer nanomicrosphere product with uniform and controllable size and preparation method thereof
CN102417552A
Preparation method of monodisperse large size carbon ball
CN102431996A
Catalase immobilizing gelatin-silicon dioxide hybrid microsphere preparation method
CN106497911A
Chitosan microspheres prepared from chitosan solution with pH value of 6-8 and preparation method of chitosan microspheres
CN111748109A
Cited By
Method for preparing submillimeter zirconia microspheres
CN120117896A